2022
DOI: 10.1093/bmb/ldac028
|View full text |Cite
|
Sign up to set email alerts
|

Cancer survivors and adverse work outcomes: associated factors and supportive interventions

Abstract: Introduction The number of cancer survivors in a working age is rising. An awareness of factors associated with adverse work outcomes, and of supportive interventions, is needed. Sources of data A narrative review of research obtained via several databases, including Medline and PsycINFO, was conducted. Areas of agreement A range of factors is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…A literature review found that several individual, work-related, and healthcare/society system factors were associated with prolonged sick leave and disability pension post cancer, cancer-related symptoms amongst other aspects. 42 An event of falling, leading to a bone fracture, was described. Patients with chemotherapy-induced neuropathy have been seen to be overrepresented in accidents.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review found that several individual, work-related, and healthcare/society system factors were associated with prolonged sick leave and disability pension post cancer, cancer-related symptoms amongst other aspects. 42 An event of falling, leading to a bone fracture, was described. Patients with chemotherapy-induced neuropathy have been seen to be overrepresented in accidents.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with cancer who are self-employed, non-regularly employed or employed by small- and medium-sized enterprises may not be able to take sick leave owing to economic circumstances. Sick leave is more common in European countries, and in certain countries, insurance covers wages during sick leave ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, support at work, which was directly linked to stable employment conditions [35], signi cantly in uenced the approach to RTW. There is a consensus in the literature on the importance of the role played by employers and co-workers in facilitating survivors' successful RTW [14]. Open and regular communication between the workplace and the person with cancer, both before and during their RTW, allowed shared understanding of ongoing challenges, including functional, cognitive and psychological implications, as well as recovery timeframes [29].…”
Section: Discusionmentioning
confidence: 99%
“…Survivors also experience multiple long-term work limitations and are less productive than the general population due chronic side effects caused by treatments and the disease itself [13]. Because there is no comprehensive guidance on the RTW or adaptations to survivors' health status on reinsertion in the labor force [14], a signi cant proportion of these individuals are unemployed, retire early, or change jobs more often than their counterparts without cancer [15]. Barriers can also include bureaucracy, emotional needs, and uncertainty.…”
mentioning
confidence: 99%